Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.

Proton conductivity in a copper(II) bipyridine glycoluril complex: the synergistic role of coordinated water and hydrogen-bonded networks - Khatavkar, Medhavi D.; Panday, Rishukumar; Singh, Mayank U.; Kurungot, Sreekumar; Kumbhar, Avinash S. (Inorganica Chimica Acta, 2026)
A dinuclear complex of copper(II) and bipyridine glycoluril (BPG) ligand is synthesized, characterized, and structurally examined by single-crystal X-ray diffraction. The complex [Cu2(BPG)2(NO3)2(H2O)4](NO3)2 center dot 5H2O (complex (1)) further forms a supramolecular network sustained by H-bonds between NH/C=O of BPG, coordinated/free water molecules, and nitrate anions. The complex exhibits a proton conductivity of 5.99 x 10_ 3 S center dot cm_ 1 at 90 degrees C and 95 % relative humidity (RH) with activation energy value Ea 0.35 eV, suggesting the Grotthuss proton transport mechanism. This value is consistent with those reported for proton-conducting systems in which coordinated water molecules play a critical role in facilitating efficient proton hopping across hydrogen-bonded networks.
Keywords: Coordinated water; Copper(II) complex; H -bonding; proton conduction; Supramolecular networks